Blood vessel-on-a-chip examines the biomechanics of microvasculature. Issue 1 (24th November 2021) - Salipante, Paul F.; Hudson, Steven D.; Alimperti, Stella
Abstract : We use a three-dimensional (3D) microvascular platform to measure the elasticity and membrane permeability of the endothelial cell layer. Abstract : We use a three-dimensional (3D) microvascular platform to measure the elasticity and membrane permeability of the endothelial cell layer. The microfluidic platform is connected with a pneumatic pressure controller to apply hydrostatic pressure. The deformation is measured by tracking the mean vessel diameter under varying pressures up to 300 Pa. We obtain a value for the Young's modulus of the cell layer in low strain where a linear elastic response is observed and use a hyperelastic model that describes the strain hardening observed at larger strains (pressure). A fluorescent dye is used to track the flow through the cell layer to determine the membrane flow resistance as a function of applied pressure. Finally, we track the 3D positions of cell nuclei while the vessel is pressurized to observe local deformation and correlate inter-cell deformation with the local structure of the cell layer. This approach is able to probe the mechanical properties of blood vessels in vitro and provides a methodology for investigating microvascular related diseases.